Residual urinary Incontinence after Successful Repair of Obstetric Fistula (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): Aim of the study was to identify the risk factors in those women who remain with incontinence after successful fistula repair.Materials & method: The women admitted in Dhaka Medical College Hospital with obstetrical genitourinary fistula were the study population.A observational study was done with all women having successful repair. They were asked to return for a follow-up appointment, 3 months after discharge . Women were examined and questioned at discharge and at follow up appointment. A structured questionnaire were used and information entered into a database.Results: Women who returned for follow-up 3 month postsurgery were included in predictors of closure analyses. Small bladder size (ARR 3.7; 95% CI 1.211.8), severe scarring (ARR 1.2; 95% CI 1.12.7), urethral involvement (ARR 7.3; 95% CI 3.31.46), were predicted failed fistula closure. Women with a closed fistula at 3 month follow-up were included in predictors of residual incontinence analyses .Conclusion:The prognosis for genital fistula closure is related to preoperative bladder size, previous repair, vaginal scarring, and urethral involvement.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 86-91